2010
DOI: 10.1111/j.1471-1842.2009.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication: a library’s local response to HIV/AIDS in Zambia

Abstract: Objective: To document and describe the University of Zambia Medical library's responses to the fight against HIV ⁄AIDS in Zambia. Methods: The methodology adopted was a case study approach combined with an analysis of the literature such as annual reports and official documents. This was augmented by personal reflections of the author having worked at the Medical Library. Results: The University of Zambia Medical library has over the years instituted and implemented HIV ⁄AIDS information provision programmes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In this unique case, librarians become peace makers and first responders for community safety. Lastly, Kanyengo (2010) explains how the University of Zambia Medical Library fought against the HIV/AIDS crisis in Zambia by offering information literacy skills programs and developing collections that were accessible for the public and researchers. They included information and materials related to disease prevention, treatment, and medical and social supports for patients.…”
Section: La Revue Canadienne Des Sciences De L'information Et De Biblothéconomiementioning
confidence: 99%
“…In this unique case, librarians become peace makers and first responders for community safety. Lastly, Kanyengo (2010) explains how the University of Zambia Medical Library fought against the HIV/AIDS crisis in Zambia by offering information literacy skills programs and developing collections that were accessible for the public and researchers. They included information and materials related to disease prevention, treatment, and medical and social supports for patients.…”
Section: La Revue Canadienne Des Sciences De L'information Et De Biblothéconomiementioning
confidence: 99%
“…The crisis category includes studies concerned with health crises, with publications on epidemics of various types, such as HIV/AIDS (Kanyengo, 2010), highly pathogenic avian influenza (Keselman et al, 2010), foot-and-mouth disease (Hagar, 2010b) or enterohemorrhagic Escherichia coli, EHEC (van Velsen et al, 2012). The articles in the health crisis category discussed various aspects of such a crisis, as well as information behavior of individuals while seeking information, or of systems managing the crisis (Aedo et al, 2010).…”
Section: Types Of Described Crisis Situationsmentioning
confidence: 99%
“…Several studies have reported the role of librarians in the dissemination of health information in African libraries. Kanyengo (2010) reported that the University of Zambia Medical Library had established health information provision programs, including the provision of information in various formats in addition to capacity building for librarians in health information literacy skills. Ntlotlang and Grand (2016) also reported that public libraries in Botswana had organized both print and electronic health information sources for the provision of accurate and useful health information to members of the community.…”
Section: Role Of Librariansmentioning
confidence: 99%